Discharge coefficients for specific grated inlets. Influence of the Froude number. Issue 7 (8th August 2020) - Cosco, Chiara; Gómez, Manuel; Russo, Beniamino; Tellez-Alvarez, Jackson; Macchione, Francesco; Costabile, Pierfranco; Costanzo, Carmelina
ABSTRACT: Surface drainage systems play a key role in the urban system. To assess the flow intercepted by inlets, some approaches use recent experimental campaigns or are based on orifice or weir formulas. In this work, real scale experimental campaigns are used to define discharge coefficients to provide information for practitioners and inlet manufacturers. Tested discharge values range between 25–200 l/s whereas transversal and longitudinal slopes range from 0–4% and 0–10% respectively. Three grated inlets have been analyzed obtaining values of discharge coefficients in situations for which the flow completely covers the grates. Discharge coefficient ranges for supercritical flow conditions have been obtained and the strong relationship with the upstream Froude number has been highlighted. Considering the orifice approach, the discharge values range between 0.055–0.294, 0.033–0.431 and 0.054–0.423 for the Barcelona1, Meridiana and E-25 grated inlets respectively. Conversely, for weir assumption, the coefficients range between 0.009–0.244, 0.003–0.245 and 0.006–0.286.